Roles of Integrins in Gastrointestinal Cancer Metastasis - Hou, Sicong; Wang, Jiaxin; Li, Wenqian; Hao, Xin; Hang, Qinglei (Frontiers in Molecular Biosciences, 2021)
Integrins are a large family of heterodimeric transmembrane receptors which mediate cell adhesion and transmit signals to the cell interior. The mechanistic roles of integrins have long been an enigma in cancer given its complexity in the regulation of different cellular behaviors. Recently, however, increasing researches are providing new insights into its function and the underlying mechanisms, which, collectively, include the altered integrin expression in cancer progression, the influences of integrin on the cell proteome pattern, the aberrant signaling pathways. Many studies have also demonstrated the potentiality of integrins as therapeutical targets in cancer treatment. In this review, we have summarized these recent reports and put a particular emphasis on the dysregulated expression of integrins and how they regulate related signaling pathways to facilitate the metastasis progression of gastrointestinal cancer, including gastric cancer (GC) and colorectal cancer (CRC), which will address the important roles of integrins in gastrointestinal cancer.